Synthesis of 3'-modified xylofuranosyl nucleosides bearing 5'-silyl or -butyryl groups and their antiviral effect against RNA viruses - Bege, Miklós; Leiner, Krisztina; Lovas, Miklós; Pető, Réka; Bereczki, Ilona; Hodek, Jan; Weber, Jan; Kuczmog, Anett; Borbás, Anikó (European journal of pharmaceutical sciences, 2025)
D-xylofuranosyl nucleoside analogues bearing alkylthio and glucosylthio substituents at the C3'-position were prepared by photoinitiated radical-mediated hydrothiolation reactions from the corresponding 2',5'-di-O-silyl-3'-exomethylene uridine. Sequential desilylation and 5'-O-butyrylation of the 3'-thiosubstituted molecules produced a 24-membered nucleoside series with diverse substitution patterns, and the compounds were evaluated for their in vitro antiviral activity against three dangerous human RNA viruses, SARS-CoV-2, SINV and CHIKV. Eight compounds exhibited SARS-CoV-2 activity with low micromolar EC50 values in Vero E6 cells, and two of them also inhibited virus growth in human Calu cells. The best anti-SARS-CoV-2 activity was exhibited by 2',5'-di-O-silylated 3'-C-alkylthio nucleosides. Twelve compounds showed in vitro antiviral activity against CHIKV and fourteen against SINV with low micromolar EC50 values, with the 5'-butyryl-2'-silyl-3'-alkylthio substitution pattern being the most favorable against both viruses. In the case of the tested nucleosides, removal of the 2'-O-silyl group completely abolished the antiviral activity of the compounds against all three viruses. Overall, the most potent antiviral agent was the disilylated 3'-glucosylthio xylonucleoside, which showed excellent and specific antiviral activity against SINV with an EC50 value of 3 μM and no toxic effect at the highest tested concentration of 120 μM.
Keywords: Chlorocebus aethiops; Nucleoside analogue antivirals; Humans; Nucleosides; nukleosidy; Severe acute respiratory syndrome coronavirus (SARS-CoV-2); Vero buňky; RNA-viry; lidé; zvířata; Photochemical thiol-ene reaction; Cercopithecus aethiops; Sindbis virus (SINV); RNA Viruses; antivirové látky; Chikungunya virus (CHIKV); Antiviral Agents; Animals; SARS-CoV-2; Vero Cells